IOT BASED SOLAR POWER MONITORING SYSTEM - Aditi Mangore; Swapnali Chougale; Mayuri Palekar; Kunal Bhosale; Sushant Kadam; Kiran Kshirsagar; Mr. S. U. Bagwan (International Journal of Innovations in Engineering Research and Technology, 2022)
Today’s generation of electricity is the basic need of everyone’s life. We need electricity heating, lighting and so many things. Day by day energy consumption is getting rapidly increased whereas resources is decreasing. There are two ways of electricity renewable and nonrenewable and in which solar power is renewable which get naturally. Solar power is a cheaper and free source and highly recommend for generation of electricity.Solar energy produced by sun’s light and generates the electricity. The IOT has a vision and it’s allows the object to be sensed and control remotely into the computer based system and they resulting in improved accuracy. This technology has many applications like solar cities, smart villages and so on. And this technology working anywhere over the internet. In our researching we are working on a model based on IOT technology that allows for smart solar power monitoring system